The impact of dynamic neuromuscular stabilization on the variability of heart rate variability in professional weight lifters and judoists - Belicka, P.; Liska, D.; Pupis, M.; Gurín, D. (Zdravotnícke listy, 2021)
Introduction: The autonomous nervous system (ANS) is the main regulatory system that maintains the integrity of the organism as a whole. Respiratory physiotherapy often forms a significant part of the training of athletes. Respiratory rate significantly affects ANS activity. Our study aimed to test the effect of dynamic neuromuscular stabilization (DNS) on heart rate variability based on spectral analysis. Sample: The sample consisted of 32 subjects with an average age of 21.2 participants. All athletes were from the DUKLA Military Sports Center, judo sports club, and weightlifting. Method: The subjects were examined and divided into two 15-member groups. The first group (n=15) was the sample group (EG). The second group (n=15) was the control group (CG). Both groups (EG, CG) passed the initial SA VSF examinatin immediately after training. After the initial examination, the EG practiced the DNS concept (20 minutes of exercise) and a standard report was obtained. After exercise, a reexamination of SA VSF was performed. After the initial examination, the CG performed routine activities normally after training. Results: In the EG, after the DNS concept exercise, there was a statistically significant increase in the spectral performance of the HF component in the leg and closing leg positions compared to the CG. The standing component after the DNS exercise in the EG did not show a statistically significant increase over the CG. In the EG, after the DNS exercise, there was a statistically significant increase in total power. Conclusion: According to our study, the concept of dynamic neuromuscular stabilization was associated with a faster return of selected and tested components in the spectral analysis to physiological values and may be beneficial for athletes in the regeneration phase.